PHP Hacks - Herrington, Jack (O'Reilly, 2011)
Programmers love its flexibility and speed; designers love its accessibility and convenience. When it comes to creating web sites, the PHP scripting language is truly a red-hot property. In fact, PHP is currently used on more than 19 million web sites, surpassing Microsoft's ASP .NET technology in popularity. Not surprisingly, this surge in usage has resulted in a number of PHP books hitting the market. Only one, though, takes the language beyond traditional Web programming and into mapping, graphing, multimedia, and beyond: PHP Hacks.